Alternative Performance Measurement for Road Management Agencies Using Data Envelopment Analysis Method - Soemardi, Biemo W; Fajri, Agung R. (Jurnal Teknik Sipil, 2013)
Abstract. Performance assessment is the most important phase in each organization cycle to determine whether the organization has been functioning in accordance to the fundamental purpose of the organization existence. This is also true for the National Road Implementation Agencies (BBPJN/BPJN) as the technical supporting units of the Directorate General of Bina Marga - Ministry of Public Works that are responsible for the maintenance and functioning of the national roads in Indonesia. As public institution, currently BBPJNs and BPJNs are accountable for their performances and to be assessed in accordance to government assessment mechanism using Performance Report of Government Institution - LAKIP. Departing from some weakness on the current mechanism, this paper is to discuss the development a performance assessment model using DEA (Data Envelopment Analysis) approach as a complementary model to the existing performance measurement model. Using DEA approach, relative efficiency amongst road agencies can be compared, which will then can be utilized as the basis for decision by the Directorate General of Bina Marga on BBPJN/BPJNâs future workplan and budgeting.Abstrak. Pengukuran kinerja merupakan tahap yang paling penting dalam setiap siklus organisasi untuk mengetahui apakah organisasi tersebut telah berfungsi dengan baik sesuai dengan tujuan keberadaannya. Hal serupa juga berlaku bagi Balai dan Bali Besar Pelaksanaan Jalan Nasional, yang merupakan organisasi di lingkungan Direktorat Jenderal Bina Marga - Kementerian Pekerjaan Umum yang berfungsi dan bertanggungjawab terhadap pemeliharaan dan penyelenggaraan jalan nasional di Indonesia. Sebagai instansi publik, saat ini kinerja BBPJN dan BPJN perlu dinilai dan dituntut pertanggungjawabannya melalui mekanisme Laporan Kuntabilitas Kinerja Instansi Pemerintah (LAKIP). Berangkat dari kelemahan-kelemahan LAKIP, makalah ini membahas pengembangan model penilaian kinerja dengan pendekatan analisa selubung data - DEA, sebagai model pendukung untuk menilai kinerja BBPJN/BPJN. Penggunaan pendekatan DEA, efisiensi relatif antara Balai/Balai Besar dapat dibandingkan,Â  yang selanjutnya dapat diguakan sebagai landasan pengambilan keputusan bagi Direktorat Jenderal Bina Marga untuk menyusun rencana kerja dan anggaran mendatang bagi Balai/Balai Besar tersebut.